Proceso De Cobranza En La Empresa Cnel- Ep Un Los Rios - Valverde Castro, Glenda Liliana (2019)
The main purpose of this paper is to identify the processes that take place in the collection department of the Strategic Public Electric Company (CNEL EP) - Los Ríos Business Unit. On December 15, 2018, CNEL EP was established by decree No. 1459, as CNEL Sociedad Anónima, with the purpose of recognizing it in Ecuador as an energy distribution and commercialization company. On March 13, 2013, the former President of the Republic, Ec. Rafael Correa Delgado, approved the constitution of (CNEL EP), as the CNEL Strategic Public Electric Company in the Ecuadorian Republic, whose purpose is to grant public distribution services. and commercialization of electricity in the country, and is currently responsible for supplying electricity to millions of users. (CNEL- EP About Us, 2018).